A Framework That Shows the Process to Help Customers Understand the Value at Each Stage of Product Development - Hayashi, Yoshinori; Masuda, Koji; Haruyama, Shigeyuki (International Journal of Integrated Engineering, 2024)
New products for new markets must meet market requirements. However, in the early stage of the new product development, the market requirements cannot be accurately understood. Therefore, we believe that finding the good customers, educating them, and helping them understand the value at each stage of product development is essential. We show a framework in which the process of searching for good customers and helping the customers understand the value at each development stage of the new product for the new market. Furthermore, we discuss whether this framework can be effective in the development of new products for new markets